2016
DOI: 10.1111/nph.14038
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific phytochemical variation shapes community and population structure for specialist caterpillars

Abstract: Summary Chemically mediated plant–herbivore interactions contribute to the diversity of terrestrial communities and the diversification of plants and insects. While our understanding of the processes affecting community structure and evolutionary diversification has grown, few studies have investigated how trait variation shapes genetic and species diversity simultaneously in a tropical ecosystem.We investigated secondary metabolite variation among subpopulations of a single plant species, Piper kelleyi (Piper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
107
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(109 citation statements)
references
References 70 publications
(134 reference statements)
2
107
0
Order By: Relevance
“…It has been demonstrated that even small differences in genetic diversity (such as single amino acid substitutions) can yield large differences in chemical profiles (Kampranis et al., 2007), and several studies have found that higher intraspecific genetic diversity reduces herbivory and disease in plant populations (Hughes, Inouye, Johnson, Underwood, & Vellend, 2008). Moreover, emerging evidence has demonstrated how variation in intraspecific chemodiversity influences community diversity among different trophic interactions (Glassmire et al., 2016; Richards et al., 2015). In the context of this study, it is important to note the similarity between clustering patterns derived from genetic and metabolite data in addition to noting evidence that some diseased mountain subpopulations (Figure 1) have lower genetic and chemical diversity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that even small differences in genetic diversity (such as single amino acid substitutions) can yield large differences in chemical profiles (Kampranis et al., 2007), and several studies have found that higher intraspecific genetic diversity reduces herbivory and disease in plant populations (Hughes, Inouye, Johnson, Underwood, & Vellend, 2008). Moreover, emerging evidence has demonstrated how variation in intraspecific chemodiversity influences community diversity among different trophic interactions (Glassmire et al., 2016; Richards et al., 2015). In the context of this study, it is important to note the similarity between clustering patterns derived from genetic and metabolite data in addition to noting evidence that some diseased mountain subpopulations (Figure 1) have lower genetic and chemical diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Eois could have diversified along phytochemical niche axes that were not quantified (Glassmire et al. ), which would also support the perspective that diversification in this group is driven by ecological opportunity associated with synergistic effects among multiple adaptive zones (Wilson et al. ).…”
Section: Discussionmentioning
confidence: 78%
“…) and even within a single species (Glassmire et al. ). Thus, Eois could have diversified along phytochemical niche axes that were not quantified (Glassmire et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Piper, prenylated benzonic acid, chromene, and dimeric chromane at concentrations higher than 10% of dry weight of leaf material that compounds have synergistic or additive effect against herbivore attack also have been reported. In addition, concentration of these metabolites is correlated with increasing elevation in relation with UV exposure and photoactive properties, and more toxic plants support a lower diversity of specialist herbivores [81].…”
Section: Pure and Applied Biogeographymentioning
confidence: 99%